ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS’ MATHEMATICAL THINKING DISPOSITION BASED ON GENDER DIFFERENCES - Muzdalipah, Ipah; Rustina, Ratna; Somatanaya, Anak Agung Gde (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
Data from the Indonesian Ministry of Education shows that the number of female teachers currently exceeds male, even at the junior high school level in Tasikmalaya the ratio is almost 2:1. Another fact is that applicants for mathematics teacher candidates at Faculty of Teacher Training and Education are dominated by women, for example at Siliwangi University the ratio of female to male mathematics teacher candidates has currently reached 4:1. It is also strongly suspected that since high school, mathematics enthusiasts have been dominated by women. This gap raises suspicions that there are differences in students' perceptions of mathematics learning based on gender identity and mathematical disposition. Students at a junior high school in Tasikmalaya Regency were taken as research subjects. The research method used was descriptive qualitative by distributing questionnaires and conducting in-depth interviews with teachers and students. The research results show that female students have stronger characters than male students. Based on the indicators of mathematical thinking disposition, the highest gap between female and male students appears in the aspects of persistence and monitoring tendency.